A Genre Analysis of Thesis Abtracts at a State University in Banten - Kosasih, Fauzy Rahman (Bina Nusantara University, 2018)
This study was conducted to identify the move structure of English abstracts of students’ thesis of a State University in public administration, management, fisheries management, and mathematics education programs, compare the consistency of these cross-disciplinary English abstracts with Bathia’s (1993) four-move structure and Swales & Feak’s (2004) five-move structure, and identify the preferred verb tense used of each move in the English abstracts of the students’ thesis. This study employed qualitative case study. Forty (40) English abstracts (10 from each discipline) were collected and analyzed. This study reveals that A-M-R move structure is the most frequent abstract move structure used in every discipline across the four disciplines with proportion 35%. Only 15% abstracts are in line with Swales & Feak’s (2004) five-move structures, and only 4 (10%) abstracts are in line with Bhatia’s (1993) four-move structure. The present tense and past tense are used in each move across the four disciplines.